2011
DOI: 10.1002/bdra.20823
|View full text |Cite
|
Sign up to set email alerts
|

Associations between periconceptional alcohol consumption and craniosynostosis, omphalocele, and gastroschisis

Abstract: Results suggest that maternal periconceptional alcohol consumption is associated with omphalocele and gastroschisis, and second and third trimester alcohol consumption are inversely associated with craniosynostosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
4
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 26 publications
6
37
4
2
Order By: Relevance
“…Most previous studies identified advanced maternal age as a risk factor for craniosynostosis [15,26,29,30] while a few [2,18], like ours, failed to show this association. This could have been due to the average young maternal age in our study and that the mothers did not make use of fertility assistance.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Most previous studies identified advanced maternal age as a risk factor for craniosynostosis [15,26,29,30] while a few [2,18], like ours, failed to show this association. This could have been due to the average young maternal age in our study and that the mothers did not make use of fertility assistance.…”
Section: Discussioncontrasting
confidence: 58%
“…Although Richardson et al [30 ]found an association between alcohol consumption after the first trimester and craniosynostosis, most previous studies fail to show such an association [26,] as was also the case in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…Infants born to mothers with reported maternal diseases, such as gestational diabetes mellitus (13,14), hypertension (15), and thyroid disorders (16,17), or adverse environmental exposure (18)(19)(20)(21)(22) during pregnancy, were excluded from this analysis because of the possible association of these factors with birth defects. The final data, involving 2,060 live-born infants, delivered after IVF with ICSI and FET, were stratified into groups according to the method of ovarian stimulation: 587 births after LPS, 1,257 births after the standard GnRH-a short protocol, and 216 births after mild ovarian stimulation.…”
Section: Study Population and Designmentioning
confidence: 99%
“…The toxic effects of alcohol on the fetus have been known for more than 40 years (39) and consumption of alcohol during pregnancy is associated with congenital birth defects (23,40) as well as unfavourable developmental (20) and neurological outcomes (16) . The consequences of low to moderate alcohol consumption during pregnancy are somewhat contradictory, with some researchers reporting no effect on child behaviour or development (17,21) whereas others report significant negative effects (5) .…”
Section: Alcoholmentioning
confidence: 99%